Housing technology of suckling cows: Hungarian and international solutions - Kosztolányiné Szentléleki, Andrea; Kovács, Levente; Szűcs, Márton; Vertséné Zándoki, Rita; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2022)
The authors’ aim was to review the housing technology of suckling cows in Hungary and variant solutions related to housing system. Summer and winter housing- and feeding systems for cows were introduced. Preparation for calving and related tasks were detailed, and calf care was described. Importance and circumstances of gentle weaning were highlighted, and equipment for handling of animals were demonstrated.